Modelagem e análise de redes sociais através de hipergrafos - Santos, Matheus H. B. dos; Vieira, Vinícius da F.; Xavier, Carolina R.; Almeida, Jussara M. de (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2024: Anais Estendidos do XXX Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2024.244389, 2024)
Complex networks are a powerful tool for understanding phenomena in the most diverse contexts. However, modeling networks as graphs, as it is centered on pairwise relationships, offers limitations in modeling many-to-many interactions, as is the case with collaboration in scientific articles. This work provides an overview of central concepts for the use of hypernetworks as models for representing social relations, discussing advantages and disadvantages, challenges and opportunities. The comparison of network and hypernetwork models built on CSBCSet, a database of scientific articles published in CSBC, allows exploring the impact of using hypernetworks to study the phenomenon of coauthorship of scientific articles.